Exploring a Gender Equality-based Sex Education Model: Case of SMA Harapan Mandiri in Medan, North Sumatra - Damanik, Fritz Hotman Syahmahita; Saliman, Saliman (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2023)
Gender-based sex education is increasingly crucial in schools, especially high school. Despite various studied models, gender-sensitive sex education remains unexplored. This research aims to identify a gender-sensitive sex education model at SMA Harapan Mandiri Medan, North Sumatra, using a qualitative approach. Data collection involves observation, interviews, and documentation, which is analyzed through reduction, presentation, and NVivo 12 Pro mapping. Results show the successful initiation of a comprehensive sex education model at SMA Harapan Mandiri. The model integrates into the curriculum, includes teacher training, fosters inclusivity, adopts anti-discrimination policies, promotes respect for diversity, educates on the negative impacts of teenage dating, involves parents, and offers information resources. The anticipated positive impact is that SMA Harapan Mandiri will become a hub for improved student mindsets through responsive sex education, fostering literacy in sexual differences, and promoting respect toward the opposite sex.